Peran Ekstrakurikuler Keagamaan dalam Meningkatkan Kesadaran Beragama Siswa-Siswi Mts Puspa Bangsa Kecamatan Cluring - Hendro Juwono; Mar Syahid (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
This research aims to determine the forms of religious extracurricular activities that can increase religious awareness and determine the factors inhibiting extracurricular activities in increasing religious awareness among students at MTS Puspa Bangsa, Cluring District. The method applied in this research is descriptive qualitative research. Data collection techniques used include observation, interviews and documentation. The data analysis technique used is interactive analysis. The research results show that the implementation of religious extracurricular activities at MTS Puspa Bangsa, Cluring District plays an important role in increasing religious awareness and forming students' religious character through various programs such as Madrasah Diniyah, sholawat, kiroah, muhadharah, hadrah training, as well as tafsir and tahfidz. Despite facing obstacles such as limited time, facilities, student motivation, parental support, financial constraints, and a shortage of teaching staff, it is hoped that continuous efforts from the school and the support of all related parties can overcome these obstacles and ensure the sustainability and success of this program.